The Importance of Thrombophilic Factors in Early Pregnancy Losses - Şen, Serdar; Hızlı, Deniz; Taşçı, Yasemin; Dilbaz, Serdar (Fırat University, 2013)
Objective: The aim of the present study was to investigate the role of thrombophilic factors in fetal losses at 10-16 gestational weeks. Materials and Methods: Between April 2003 and May 2004, 50 women who were hospitalized due to fetal loss at 10-16 gestational weeks were defined as study group and 50 women with at least 1 healthy term infant and had no previous miscarriage history were defined as control group. Activated protein C resistance, anti-thrombin III deficiency, protein S deficiency and the presence of anticardiolipin antibodies were evaluated. Chisquare test and independent sample t-test were used for statistical analysis. The cut-off value for statistical significance was set at p 10 gestational weeks suggests that thrombophilia screening should be a part of the management of these patients.

Amaç: 10-16 gebelik haftası arası meydana gelen fetal kayıplarda kalıtımsal ve kazanılmış trombofilik faktörlerin rolünün incelenmesi. Gereç ve Yöntem: Nisan 2003-Mayıs 2004 tarihleri arasında 10-16 gebelik haftasında fetal kayıp nedeniyle Ankara Etlik Zübeyde Hanım Doğumevi Erken Gebelik Servisine yatırılan 50 hasta çalışma grubu olarak, daha önce gebelik kaybı öyküsü olmayan ve en az bir sağlıklı doğum yapmış 50 kadın kontrol grubu olarak kabul edildi. Tüm hastalarda aktive protein C resistansı, protein S ve antitrombin 3 eksikliği ve antikardiyolipin antikor pozitifliği araştırıldı. Her iki grup arasında bu parametreler açısından fark olup olmadığı bağımsız T testi, ki-kare testi kullanılarak incelendi. P
Erken Gebelik Kayıplarında Trombofilik Faktörlerin Önemi